Biological pre-treatment of rubber wood with white rot fungi for bioethanol production - Nazarpour, Forough Kalaei (2011)
In the present study, rubber-wood (Hevea brasiliensis) was used as a raw material for bioethanol production. The goal of this study was to investigate the efficiency of biological pretreatment using Ceriporiopsis subvennispora ATCC 90467, Tranietcs versicolor A TCC 20869, and a mixed culture of C subvennispora and T. versicolor for the conversion of rubber-wood to bioethanol. There are numerous pre-treatment methods but they often lead to the losses of carbohydrate, generate toxic wastes that inhibit enzymatic hydrolysis and consume a lot of energy. In contrast. a biological pretreatment method using fungi is advantageous because of low energy demand and mild treatment conditions but requires a long treatment time. Change in chemical composition, structural modification and susceptibility to enzymatic saccharification and ethanol production in the degraded wood were analyzed. Results of this study showed that the selective lignin-degrading fungus C. subvermispora had greater selectivity for lignin degradation with the highest lignin and hemicellulose loss at 45.06 % and 42.0~ %, respectively after 90 days among the tested samples. Meanwhile the cellulose loss was very low (9.50 %) compared to those of T. versicolor and mixed culture. X-ray analysis showed that pretreated samples had a higher crystallinity than untreated samples. The sample pretreated by C. subverntispora presented the highest crystallinity of all the samples which might be caused by the selective degradation of amorphous components. Fourier transform infrared (FTIR) spectroscopy demonstrated that the content of lignin and hemicellulose decreased in the biological pre-treatment process. The influence of particle size (0.25, 0.50, and I.on mrn) on pretreatment effectiveness by C subvcnnispora was also examined by X-ray and chemical analysis. The rubber-wood with particle size 1 mrn was efficiently degraded to provide better aeration/respiration opportunities as compared to smaller particle size of samples. To evaluate the biological pre-treatment, cellulose in the pretreated woods was hydrolyzed using cellulase (Celluclast 1.5 L, produced by Trichoderma rcesciv and ~-glucosidase (Novozyrne 1~~, produced by AspcIgillus niger) at 50 "C far 16~ hours and the released sugars were converted to biocthanol by simultaneous saccharification and fermentation process (SSF) USing yeast Saccharoll1yces ccrcvisiae DSA at 37 DC for 120 hours. A study on hydrolysis of rubberwood treated with C subvermispora. T. versicolor, and mixed culture for l) 90 days resulted in an increase sugar yield about 27.67 (Yu, 16.23 %, and 14.20 %, respectively as compared to untreated rubber-wood (2.88 (Ytl). The sample obtained using the best pretreatment (sample pretreated by C subvermisporai was used for bioethanol production. After 120 hours, the maximum bioethanol concentration and yield were 17.9 giL and 53 %, respectively. The results obtained demonstrate that white rot fungus C. subevermispora is a suitable fungus for improving the enzymatic hydrolysis and bioethanol production of rubber-wood. The results also demonstrated that rubber-wood is a potential raw material for bioethanol production.